2016
DOI: 10.18240/ijo.2016.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraocular pressure measurements with different contact tonometers in young healthy persons

Abstract: Both I-Care and Tono-Pen tonometers overestimated IOP compared with the GAT values. Either the I-Care or Tono-Pen tonometer could be used instead of GAT because there was no significant difference between their results. Higher CCT values (>555 µm) were associated with overestimated IOP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Eraslan et al 1 concluded that “Because Tono-Pen (TP) measurements were lower than Goldmann applanation tonometer (GAT) measurements and non-contact tonometer measurements were higher than GAT measurements, patient follow-ups, treatment strategies, and surgery plans must be organized taking these differences into consideration”. The results in this report are similar to a recent report by Galgauskas et al 2 In fact, the use of different kinds of tonometer can result in different measures values and this has to be kept in mind by practitioners. The correlation study can be useful for checking the variability of the tool.…”
Section: Dear Editorsupporting
confidence: 90%
“…Eraslan et al 1 concluded that “Because Tono-Pen (TP) measurements were lower than Goldmann applanation tonometer (GAT) measurements and non-contact tonometer measurements were higher than GAT measurements, patient follow-ups, treatment strategies, and surgery plans must be organized taking these differences into consideration”. The results in this report are similar to a recent report by Galgauskas et al 2 In fact, the use of different kinds of tonometer can result in different measures values and this has to be kept in mind by practitioners. The correlation study can be useful for checking the variability of the tool.…”
Section: Dear Editorsupporting
confidence: 90%
“…Previous studies found a nonsignificant difference between Goldmann Aplannation Tonometery and Tonopen measurements. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rebound ters are well-suited for use with children, elderly patients, and patients with cog physical disabilities who cannot tolerate other IOP measurement methods. Rebo nometers enable a rapid measuring process, taking just a few seconds per eye, a compact, portable design allows for use in a wider range of se ings compared to Similar to GAT, the accuracy of rebound tonometry can be affected by corne ness and curvature, overestimating IOP in patients with thicker corneas [22][23][24]. curacy and consistency of IOP reading also depend on patient cooperation, blink ing measurements, and corneal hysteresis [25].…”
Section: Handheld Tonometersmentioning
confidence: 99%